GAMELAN SUNARENG BANJAR ADAT ANTA, DESA TANGLAD, KECAMATAN NUSA PENIDA, KABUPATEN KLUNGKUNG - I Wayan Sukadana; Agus Ngurah Feryarta (WIDYANATYA, 2022)
ABSTRACT Gamelan Sunareng is believed by the people of Banjar Adat Anta, Tanglad Village, Nusa Penida District, Klungkung Regency to have magical powers and therefore is very sacred at Puseh Temple Banjar Adat Anta, Tanglad Village. The approach applied is qualitative. Based on the results of the study, it can be seen as follows: Instrumental forms include: two Tungguh Gangsa, Kendang, Ceng-ceng ricik, Tawa-tawa, and Kempul. Musicality includes: musical elements and Gending Structure. The process of performing the presentation of Gamelan Sunareng at Piodalan at Puseh Temple, namely: exercises, Mereresik activities, preparing facilities, offering facilities, ritual of nunas tirta, squeezing Gamelan, making offerings in circles, sprinkling water, presenting Gamelan Sunareng and Gandrung dance, and closing with prayers. ABSTRAK Gamelan Sunareng diyakini masyarakat Banjar Adat Anta, Desa Tanglad, Kecamatan Nusa Penida, Kabupaten Klungkung memiliki kekuatan magis oleh karenannya sangat disakralkan di Pura Puseh Banjar Adat Anta, Desa Tanglad. Pendekatan yang diterapkan bersifat kualitatif. Berdasarkan hasil penelitian dapat diketahui sebagai berikut: bentuk Instrumental meliputi: dua Tungguh Gangsa, Kendang, Ceng-ceng ricik, Tawa-tawa, dan Kempul. Musikalitas meliputi: unsur-unsur musikal dan Struktur Gending. Proses pelaksanaan penyajian Gamelan Sunareng pada Piodalan di Pura Puseh yaitu: latihan, kegiatan Mereresik, mempersiapkan sarana, menghaturkan sarana, ritual nunas tirta, memeras Gamelan, menghaturkan sesaji di kalangan, memercikan tirta, penyajian Gamelan Sunareng dan tari Gandrung, dan ditutup dengan persembahyangan.